ANALISIS PENGARUH PROMOSI DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK KECANTIKAN DI SUBUR FASHION CENTER - Ni Putu Ayu Sri Dewi Andayani; Febsri Susanti (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to analyze the influence of promotion and price on purchasing decisions for beauty products at Subur Fashion Center. The research uses a quantitative method, with data collected through questionnaires distributed to consumers. Data analysis techniques include validity tests, reliability tests, multiple linear regression analysis, and t-tests to examine the effect of each variable. The results indicate that promotion and price significantly influence purchasing decisions. Attractive promotions increase consumer buying interest, while competitive pricing creates positive perceptions of product value. The effective combination of promotion and pricing positively impacts consumer purchasing decisions. This study suggests that Subur Fashion Center should continuously optimize its promotion strategies and pricing policies to enhance product attractiveness and customer satisfaction.